2018
DOI: 10.1097/md.0000000000010825
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous double superficial mixed gastrointestinal mucus phenotype gastric cancer with gastritis cystica profunda and submucosal lipoma

Abstract: The diagnosis and treatment of synchronous double superficial gastric cancer with GCP and submucosal lipoma is challenging. In addition, elastic fiber staining and immune marker staining is effective and should be considered for diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Based on this mechanism, we suspected that IFP growth under the mucosa triggered GCP formation in this case. In some reports, GCP has been considered as a high-risk factor for gastric cancer, and thus, its subsequent biological behavior and in uence on patient prognosis need to be studied [10]. (2) Inverted hyperplastic polyp (IHP).…”
Section: Diagnosismentioning
confidence: 99%
“…Based on this mechanism, we suspected that IFP growth under the mucosa triggered GCP formation in this case. In some reports, GCP has been considered as a high-risk factor for gastric cancer, and thus, its subsequent biological behavior and in uence on patient prognosis need to be studied [10]. (2) Inverted hyperplastic polyp (IHP).…”
Section: Diagnosismentioning
confidence: 99%
“…Lipoma is located between the mucosal layer and the muscularis propria, which is adjacent to the lesion of early gastric cancer, indicating that these are usually concomitant tumors. [5][6][7] Huang et al [8] reported a case of gastric cancer with gastrointestinal lipoma with simultaneous doublesurface mixed gastrointestinal mucus phenotype, which suggests that the possibility of synchronous tumor should be considered in the clinic. In this study, we found 2 cases of duodenal lipomas with gastric cancer, which is consistent with previous studies.…”
Section: Potential Clinical Significance Of Duodenal Lipomamentioning
confidence: 99%
“…[4] Moreover, previous reports have described chemical lipoma complicated with gastric adenocarcinoma and signet ring cell carcinoma. [5][6][7][8][9] Therefore, attention should be devoted to lipoma in the clinic. However, duodenal lipoma is not easy to diagnose; as such, an effective diagnostic method(s) is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,16,17 However, it is unclear whether there is a definite relationship and a specific mechanism, and these findings need to be confirmed by further studies. Whether GCP is regarded as benign or precancerous is still unclear, 18,19 and long-term follow-up is warranted.…”
mentioning
confidence: 99%